Islamic Religious Education Teachers' Strategies in Building Self-Esteem in Students at State Vocational School 4, Jambi City - Muhamad Iqbal; Neneng Hasanah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in building students’ self-esteem at SMK Negeri 4 Kota Jambi. The research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, while data analysis followed Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The findings reveal that PAI teachers implement various strategies to enhance students’ self-esteem, such as providing positive reinforcement, instilling Islamic values, applying individual approaches, creating a conducive learning environment, and encouraging active participation. Furthermore, the strategies include role modeling (uswah hasanah), participatory learning, individual guidance, self-potential development, and spiritual approaches. These strategies significantly improve students’ confidence, courage, and active engagement in the learning process. Therefore, PAI teachers play a crucial role in fostering students’ self-esteem through a holistic approach encompassing psychological, social, and spiritual aspects.